572 Effect of Enzymatically Modified Isoquercitrin, a Flavonoid, on Symptoms of Japanese Cedar Pollinosis - Tanaka, Toshio (World Allergy Organization Journal, 2012)
BACKGROUND: The prevalence of allergic diseases has increased all over the world during the last 2 decades. Dietary change is considered to be one of environmental factors that cause this increase and worsen allergic symptoms. If it is the case, an appropriate intake of foods and beverages with antiallergic activity is anticipated to prevent the onset of allergic diseases and ameliorate allergic symptoms. Flavonoids, ubiquitously present in vegetables, fruits or tea possess antiallergic and antioxidant effects, so that we examined the efficacy of a flavonoid on clinical symptoms of Japanese cedar pollinosis. METHODS: We investigated the efficacy of enzymatically modified isoquercitrin (EMIQ), a quercetin glycoside, to relieve symptoms of Japanese Cedar pollinosis by 3 different clinical trials. In either trial patients were randomly assigned to the EMIQ group or the placebo group and took one capsule containing EMIQ plus corn starch or corn starch only twice a day. The efficacy was evaluated with the total symptom, medication or QOL score. Study 1 (reference 1) and 2 (reference 2); EMIQ (100 mg/day) versus placebo, for 8 weeks, started after (study 1) and before (study 2) the onset of pollen release, Study 3; EMIQ (200 mg/day) versus placebo, for 4 weeks, started after the onset of pollen release. RESULTS: In study 1 and 2, during the entire study period, ocular + medication score for the EMIQ group was significantly lower (P < 0.05) than that of the placebo group. When limited to the period, total symptom + medication score for the EMIQ group was significantly lower than that for the placebo group in all 3 studies. CONCLUSIONS: These results indicate that intake of EMIQ, a quercetin glycoside proved to be effective for the relief of symptoms caused by Japanese cedar pollinosis.